Does active eating influence dyspnea and pulmonary function tests in COPD? - Özgören, Çağla; Hacıömeroğlu, Osman; Muammer, Rasmi (My University, 2024)
Active eating is considered an effortful activity for patients with chronic obstructive pulmonary disease (COPD). Aim of study was to determine the effect of active eating on pulmonary functional capacity, dyspnea level and oxygen saturation (SpO2) in COPD patients. 40 clinically stable COPD patients who were hospitalized in Süreyyapaşa Chest Diseases and Thoracic Surgery Education and Research Hospital were enrolled. All patients were in group D according to 2016 GOLD guide. Demographic data, smoking status, body mass index, medications and additional diseases of patients were noted. The degree of dyspnea was assessed using the Modified BORG scale before and after active eating for all participants and was also measured in obese and non-obese subgroups. Spirometric parameters and SpO2 were analyzed one hour before and after active eating. In general, there was no statistically significant difference in FVC, FEV1, FEV1/FVC and SpO2 values compared to initial measurements (p>0.05). However, significant difference was observed in BORG scale evaluations for all participants (p<0.05). According to subgroups, there was no significant difference in FEV1/FVC and SpO2 results (p<0.05), but difference was found in FEV1, FVC and BORG values in non-obese group (p<0.05). In obese group, we found no difference in any of evaluated parameters (p <0.05). In conclusion, we observed no change in spirometric parameters and SpO2 level in total but there was a change in FEV1, FVC and dypnea level in non-obese goup.
Keywords: Active Eating; Chronic Obstructive Pulmonary Disease; Pulmonary Capacity; Spirometry